Comparative effectiveness of different types of female condoms: a systematic review and network meta-analysis - Abdelrahman Saeed; Omar Saeed; Munia Rajabi; Amr K. Hassan; Israa Ahmed Qutob; Mahmoud Ramadan Ebrahim; Izere Salomon; Khaled Moghib (Middle East Fertility Society Journal)
Abstract Background The female condom is a type of barrier contraception with a wide range of benefits. These benefits include significantly reducing the risk of sexually transmitted diseases and the number of unintentional pregnancies; however, their failure rates and functional performance have not been studied thoroughly. Objectives This study aimed to compare the functional performance and practical use of different types of female condoms. Methods We conducted a systematic review and network meta-analysis following the Preferred Reporting Items for Systematic reviews and Meta-analysis for Network Meta-Analyses (PRISMA-NMA) statement. We included randomized clinical trials assessing the types of female condoms in the sexually active female population using the PubMed, Scopus, and Web of Science databases. We assessed the risk of bias (RoB) in the included studies using the Cochrane risk of bias (ROB-1) tool. Results Through our literature search, 649 articles were identified, and only 11 randomized clinical trials were included. When assessing total clinical failure, Cupid condoms demonstrated noninferiority when compared to FC2 (NMA estimate: 0.79, 95% CI: − 1.09 to 2.73, p = 0.40). Regarding total condom failure, the analysis indicated no significant difference between the Cupid condom and others like V-Amour (NMA estimate: − 0.17, 95% CI: − 0.57 to 1.76, p = 0.32) or Velvet (NMA estimate: 0.69, 95% CI: − 1.62, 0.52, p = 0.32). Similarly, comparisons between Cupid and other types, such as Velvet or WC, regarding the incidence of slippage yielded nonsignificant results. These findings suggest generally consistent performance in terms of slippage across different types of condoms. Conclusion This systematic review and network meta-analysis showed the noninferiority of different types of female condoms compared to FC2 regarding their failure rates and functional performance. Our results show that female condoms are a reliable form of contraception, with minimal complications and adverse events.